2013
DOI: 10.1093/schbul/sbt054
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Neuroimaging Studies in Major Depressive Disorder With Psychotic Features: A Critical Review

Abstract: The relationship between major depressive disorder with psychotic (MDDP) features and schizophrenia has long been recognized, and the neurobiological boundaries between these disorders can nowadays be investigated using neuroimaging techniques. This article provides a critical review of such studies, addressing how they support a dimensional approach to the nosology and pathophysiology of psychotic disorders. A proportion of neuroimaging studies carried out to date indicate that MDDP subjects display structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 117 publications
1
38
0
2
Order By: Relevance
“…This is in line with several neuroimaging studies, which have revealed that schizophrenia is associated with gray matter reductions in the prefrontal cortex and white matter integrity changes in the deep frontal and temporal regions [48][49][50], whereas functional neuroimaging studies showed reduced DLPFC activation during working memory tasks in these patients [51,52]. In fact, even during rest, hypoactivity of the prefrontal cortex is observed [53].…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with several neuroimaging studies, which have revealed that schizophrenia is associated with gray matter reductions in the prefrontal cortex and white matter integrity changes in the deep frontal and temporal regions [48][49][50], whereas functional neuroimaging studies showed reduced DLPFC activation during working memory tasks in these patients [51,52]. In fact, even during rest, hypoactivity of the prefrontal cortex is observed [53].…”
Section: Discussionsupporting
confidence: 89%
“…Over recent years, several neuroimaging studies have attempted to identify the specific neural circuits implicated in the emergence of psychotic symptoms. 18,19 These studies have supported the notion that abnormalities in the salience network, interconnecting the anterior cingulate cortex and the insula, [20][21][22][23] constitute a core pathophysiological feature of psychosis. 18 Salience is the state or quality by which something stands out from its surroundings.…”
Section: Discussionmentioning
confidence: 57%
“…These areas are implicated in both depression with psychosis and schizophrenia. 40 In broader terms of affective instability, there is some convergence of evidence that alterations in amygdala activation is involved in difficulty in emotional processing, salience to emotional stimuli, and behavioral response. 23 Thus it is possible that depression (as a core dimension of psychosis) not only explains some of the commonality in biological findings across mood disorders and schizophrenia, but provides potential aetiological pathways.…”
Section: Three Pathways To Depression In Schizophreniamentioning
confidence: 99%